Impact Of Personalısed Gıftıng E-Commerce Platforms On Offlıne Retaılers And Customers - Akansha Sahgal (International Journal of Advanced Science and Technology, 2020)
India is one of the most socializing and hospitable country in the world and gifting is an inseparable part of its culture. Indians are amongst the most passionate people when it comes to giving and receiving gifts. As a part of India’s rich culture there are so many occasions where people exchange gifts, be it on a personal level or at the corporate level. But with more digitization taking place the trends in the purchasing behavior of consumers are changing. The e-commerce market of India is growing rapidly and online gifting platforms are major contributors to this growth. Moreover, the personalised gifting segment has gained a lot of traction recently and continues to grow. This has affected the traditional offline retailers a lot as their sales are continuously declining. This paper aims to understand the factors as to why the sales of offline retailers are going down and why people are preferring more and more personalised products over traditional gifts. The research was done by circulating a survey among people to understand the factors affecting their buying patterns as well as interviews with retailers and gathering secondary data from certified reports to understand the effect on the offline sales in recent years. The results of the study showed that rise in demand of online platforms was a reason for the decline in the offline sales as well as the retailers who stuck to traditional gifts faced decline in sales even more as people are preferring more of personalised gifts now.